Efficacy and safety of Tongxinluo in the treatment of stroke: a systematic review and meta-analysis of randomized controlled trials - Wu, Zhixin; Fu, Jiamei; Zhou, Yumeng; Zhou, Yabin (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluates the efficacy and safety of Tongxinluo in treating stroke.MethodsPubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure and Wanfang databases were performed to search literature from 2000 to 2024. Randomized controlled trials evaluating Tongxinluo for stroke were included. The primary outcomes were efficacy and safety. Sensitivity and subgroup analyses were conducted to assess result stability and identify sources of heterogeneity. All analyses were conducted using Review Manager 5.4 and STATA 15.1.ResultsFifty-one RCTs including 9,577 participants for analysis. Tongxinluo significantly outperformed the control group in efficacy [RR = 1.20, 95% CI (1.16, 1.25)]. Adverse event incidence between groups showed no significant difference [RR = 1.01, 95% CI (0.90, 1.12)]. Additionally, Tongxinluo significantly improved NIHSS, total cholesterol (TC), and serum hypersensitive C-reactive protein (hs-CRP) levels in stroke individuals.ConclusionTongxinluo, as an adjunctive treatment for stroke, offers superior clinical efficacy compared to conventional treatments without increasing adverse event risk. However, due to study limitations, further multicenter, large-sample RCTs are required to confirm.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/.